1993
DOI: 10.2176/nmc.33.765
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Artery Dissecting Aneurysm Rebleeding After Proximal Occlusion —Case Report—

Abstract: A 38-year-old male presented with vertebral artery dissecting aneurysm manifesting as subarachnoid hemorrhage. An attempt at trapping the aneurysm failed, so the vertebral artery could only be clipped proximally. Rebleeding occurred, resulting in death, probably due to excessive length of the dissection requiring thrombosis and/or retrograde dissection due to back pressure from the contralateral vertebral artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…До сих пор были пред-ставлены небольшие исследования эндоваскулярных методов лечения РАВБАС [3][4][5][8][9][10]. Во многих слу-чаях зарегистрировали развитие рецидива РАВБАС с или без САК после эндоваскулярного лечения [5,9,[10][11][12][13][14][15][16][17]. При расслаивающих аневризмах рецидив после лечения может быть более опасным, чем при аневризмах Берри.…”
unclassified
“…До сих пор были пред-ставлены небольшие исследования эндоваскулярных методов лечения РАВБАС [3][4][5][8][9][10]. Во многих слу-чаях зарегистрировали развитие рецидива РАВБАС с или без САК после эндоваскулярного лечения [5,9,[10][11][12][13][14][15][16][17]. При расслаивающих аневризмах рецидив после лечения может быть более опасным, чем при аневризмах Берри.…”
unclassified
“…Although internal trapping has been widely used and is thought to be effective in the treatment of ruptured VADAs [3,[17][18][19], immediate total occlusion is not always possible, and early rebleeding is not uncommon [21][22][23]. In our series, 20 % of the cases in the trapping group failed to be immediately totally occluded, and the proportion decreased to 11.1 % (2/18) at the follow-ups, which is comparable to the published results [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Thrombosis could easily develop in the pseudolumen, resulting in stenosis 4) and further occlusion of the affected artery. 7) On the contrary, two patients with ruptured dissecting aneurysm, one in the middle cerebral artery 3) and another in the VA, 6) were reported to rebleed on Day 8 and Day 18, respectively, although the initial angiography showed that the affected arteries were occluded. In the latter case, 6) the initial angiography on Day 2 revealed complete occlusion of the VA just distal to the dissecting aneurysm, whereas the second angiography on Day 15 revealed growth of the dissecting aneurysm and recanalization of the affected VA.…”
Section: Discussionmentioning
confidence: 99%